Pyrogenic carbon and carbonating minerals for carbon capture and storage (PyMiCCS) part I: production, physico-chemical characterization and C-sink potential - Meyer zu Drewer, Johannes; Vorrath, Maria-Elena; Amann, Thorben; Hartmann, Jens; De la Rosa, Jose Maria; Möllmer, Jens; Pérez-Dalí, Sara Maria; Meredith, William; Uguna, Clement; Snape, Colin; Kammann, Claudia; Schmidt, Hans-Peter; et al. (Frontiers in Climate, 2025)
Carbon dioxide removal (CDR) at gigaton-scale is essential to meet the Paris climate goals. Relevant CDR rates can only be achieved through the co-deployment of multiple CDR approaches. However, synergisms between different CDR methods and joint co-benefits beyond CDR have seldom been investigated. The combination of pyrogenic carbon (PyC) and enhanced weathering of minerals (Mi) for carbon capture and storage (CCS), in short PyMiCCS, presents a potentially synergetic and multifunctional approach that may be achieved by either co-application of biochar and rock powder to soils or the co-pyrolysis of biomass and rock powder before soil use. Here, we mixed biomass (wood; straw) with 10 to 50 wt% silicate rock powder (namely basanite or diabase) for co-pyrolysis to produce twelve different rock-enhanced (RE-)biochars. Products were subject to physico-chemical characterization, including an assessment of carbon yield and proxies for biochar persistence. Rock-enhanced biochars showed higher nutrient content, liming- and C-sink potential but lower solid-state electrical conductivity and porosity compared to pure biochars. Co-pyrolysis resulted in a coating of rock particles with secondary char but did not affect the net carbon yield. The thermal stability of wood-based RE-biochars (+10 wt% rock) was higher than that of pure woody biochars. However, the underlying mechanism and implications for biochar persistence in the environment need further investigation. Despite the addition of rock powder, the short-term release of ions from the ash fraction remains dominated by cations and anions of biogenic (biochar) origin. Therefore, it is still unclear whether the pyrogenic coating influences rock weathering. Co-pyrolysis with rock dust opens further options for designing biochar properties and to produce novel composite materials catering for multifunctional CDR.